Branding Strategy of Batik Sido Asih in Indonesia - Syaukani, Ibnu Khalid; Sumarlan, Iman (Manunggal Halim Jaya, 2026)
This study explores the branding strategy of Batik Sido Asih in Giriloyo Batik Village, Yogyakarta, focusing on how it attracts consumer interest amid competition from mass-produced batik and contemporary fashion trends. Using a qualitative descriptive approach, data were gathered through interviews with the owner, artisans, and customers, participant observation in the gallery and workshop, and documentation of digital promotional materials. Thematic analysis, following Miles and Huberman’s framework, identified key dimensions of branding based on Aaker’s Brand Equity Model: (1) brand awareness, (2) perceived quality, (3) brand associations, and (4) brand loyalty. Findings reveal that Batik Sido Asih builds strong brand awareness through consistent visual identity and active use of Instagram and TikTok. Traditional hand-drawn techniques using natural dyes sustain the perceived quality, which is openly demonstrated to consumers. Cultural storytelling and family heritage strengthen brand associations, while loyalty is fostered through personal interactions, workshops, and cultural tourism experiences. The study highlights how Batik Sido Asih integrates digital channels with traditional values, offering a model for micro-scale cultural enterprises. Theoretically, this research contributes to cultural branding literature in SMEs, while practically, it provides insights for traditional craft entrepreneurs to design authentic and competitive branding strategies in a digital marketplace.